2015
DOI: 10.3389/fnmol.2015.00008
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-dependent proteolysis in yeast cells expressing neurotoxic proteins

Abstract: Critically impaired protein degradation is discussed to contribute to neurodegenerative disorders, including Parkinson's, Huntington's, Alzheimer's, and motor neuron diseases. Misfolded, aggregated, or surplus proteins are efficiently degraded via distinct protein degradation pathways, including the ubiquitin-proteasome system, autophagy, and vesicular trafficking. These pathways are regulated by covalent modification of target proteins with the small protein ubiquitin and are evolutionary highly conserved fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 149 publications
(313 reference statements)
1
21
0
Order By: Relevance
“…cerevisiae has been successfully utilized as a model organism to explore aging research. Indeed, studies analyzing human protein orthologs, or expression of heterologous human disease-associated proteins have revealed the value of yeast as model to study molecular mechanisms of disease [2529]. We confirmed that Rpt6 is phosphorylated in yeast, and that this modification is increased upon stress.…”
Section: Introductionsupporting
confidence: 73%
“…cerevisiae has been successfully utilized as a model organism to explore aging research. Indeed, studies analyzing human protein orthologs, or expression of heterologous human disease-associated proteins have revealed the value of yeast as model to study molecular mechanisms of disease [2529]. We confirmed that Rpt6 is phosphorylated in yeast, and that this modification is increased upon stress.…”
Section: Introductionsupporting
confidence: 73%
“…Although the tardbp gene mutation is uncommon, other gene mutations related to ALS can also lead to abnormal intracellular TDP-43 levels [29,34] . Therefore, it is necessary to analyze the clearing pathway of pathological TDP-43.…”
Section: Removal Of Pathological Tdp-43mentioning
confidence: 99%
“…The autophagy mediated TDP-43 CTFs fragmentation is caused by the failure of the phagocytosis of membrane vesicles [26] , which suggested that autophagy also affected the transcription capacity of TDP-43 proteins. In addition, several studies have illustrated that TDP-43 concentration may increase toxicity in HeLa cells, suggesting that the autophagy system and the ubiquitin proteasome system may affect transcription of TDP-43 [34] . TDP-43 mitochondrial localization inhibitory peptide can also abolish cytoplasmic TDP-43 accumulation, restore mitochondrial function, prevent neuronal loss, and alleviate motor-coordinative and cognitive deficits in adult hemizygous TDP-43 M337V mice [35] .…”
Section: Removal Of Pathological Tdp-43mentioning
confidence: 99%
“…Deubiquitination of α-syn might redirect the α-syn burden toward the ALP, which is generally recognized as a more efficient α-syn degradation pathway than the UPS ( Vogiatzi et al, 2008 ). It should be noted that α-syn ubiquitination can serve as a signal for lysosome-dependent degradation ( Tofaris et al, 2011 ; Braun, 2015 ; Alexopoulou et al, 2016 ), illustrating a complex cross-talk between post-translational modifications of α-syn and cellular degradation machineries ( Choi et al, 2012 ; Haj-Yahya et al, 2013 ; Shahpasandzadeh et al, 2014 ; Tenreiro et al, 2014 ; de Oliveira et al, 2017 ). It remains unclear which α-syn degradation pathway is favored, therefore further study is needed before a viable therapeutic strategy can be designed to enhance UPS-mediated α-syn degradation.…”
Section: Targeting Pqc Defects As Potential Neuroprotective Strategiementioning
confidence: 99%